2016
DOI: 10.1016/j.ijsu.2016.07.076
|View full text |Cite
|
Sign up to set email alerts
|

Massive and recurrent diverticular hemorrhage, risk factors and treatment

Abstract: Right colon diverticulosis rather than patient characteristics and medical treatment should prompt for aggressive management with lower threshold for surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…In this study, there was no difference in the rate of early rebleeding between the definite and presumptive CDB groups. Previous studies have revealed that CDB of the right colon was a significant risk factor for rebleeding requiring surgical resection . The predilection towards right‐sided CDB in the presumptive group fight affect the rate of early rebleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, there was no difference in the rate of early rebleeding between the definite and presumptive CDB groups. Previous studies have revealed that CDB of the right colon was a significant risk factor for rebleeding requiring surgical resection . The predilection towards right‐sided CDB in the presumptive group fight affect the rate of early rebleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that CDB of the right colon was a significant risk factor for rebleeding requiring surgical resection. 34,35 The predilection towards right-sided CDB in the presumptive group fight affect the rate of early rebleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Rebleeding from diverticula after successful endoscopic hemostasis is also a critical problem and the incidence was reported to be between 10.8 % and 43.4 % 6 7 . Risk factors for colonic diverticular rebleeding have been identified: bleeding from the right colon, shock, hypertension, hyperlipidemia, and the use of NSAIDs or anti-thrombotic drugs 7 8 9 10 . However, endoscopic visibility of diverticula with bleeding has not been evaluated in association with rebleeding risk, although variety is observed in the appearance of diverticular bleeding, including active spurting from diverticula and vessel exposure in the diverticular bed.…”
Section: Introductionmentioning
confidence: 99%
“…18 Surgical intervention may be needed for patients with uncontrollable bleeding. 19,20 Therefore, endoscopic hemostasis is recommended for a colonic diverticulum with SRH; leading from this, improvement of SRH detection rate is the key for CDB management. 1,15,18 The use of a water-jet scope was introduced by Ishii et al as a safe and effective endoscopic treatment for CDB in 2010.…”
Section: Introductionmentioning
confidence: 99%